Strategy to Reduce the Use of Private Cars and Motorbikes to Campus to Support the Green Campus Program - Kurniati, Titi; Yossyafra, Yossyafra; Amirna, Rahimmah (Andalasian International Journal of Applied Science, Engineering and Technology, 2023)
The United Nation states that vehicle fuel gas emissions from the transportation sector are a significant contributor to global warming. One of the preventative steps that universities can take is to limit the use of vehicles to and within the campus environment. Andalas University as one of the largest campuses in West Sumatra is very interested in taking an active role in reducing vehicle fuel gas emissions. The first aim of this research is to observe the ratio of vehicles entering campus to the campus population, and calculate the percentage reduction in private vehicle use, in order to increase the UI green metric level. Second, identifying potential private vehicle users who will switch to using Trans Padang public transportation. Traffic volume data collection is carried out using video recordings. A questionnaire interview survey was also carried out to analyze the campus population's preference for switching to public transportation. The survey results show that the volume of vehicles entering campus is more than twelve thousand vehicles. To achieve an increase in the value of one level of the UI green metric requires a reduction in private vehicles of 63.4%. The results of the chi-square test for the variables of employment, private vehicle ownership, and monthly income influence the variable frequency of private vehicle use. Users of motorbikes, private cars, online taxis and paratransit wish to shift mode using Trans Padang, and conventional motorcycle taxi users really wish to shift mode using Trans Padang.